Herbivory and climate interact serially to control monoterpene emissions from pinyon pine forests. Issue 6 (1st June 2014) - Trowbridge, Amy M.; Daly, Ryan W.; Helmig, Detlev; Stoy, Paul C.; Monson, Russell K.
Abstract : The emission of volatile monoterpenes from coniferous trees impacts the oxidative state of the troposphere and multi‐trophic signaling between plants and animals. Previous laboratory studies have revealed that climate anomalies and herbivory alter the rate of tree monoterpene emissions. However, no studies to date have been conducted to test these relations in situ. We conducted a two‐year field experiment at two semiarid sites dominated by pinyon pine ( Pinus edulis ) during outbreaks of a specialist herbivore, the southwestern tiger moth ( Lophocampa ingens : Arctiidae). We discovered that during the early spring, when herbivory rates were highest, monoterpene emission rates were approximately two to six times higher from undamaged needles on damaged trees, with this increase in emissions due to α‐pinene, β‐pinene, and camphene at both sites. During mid‐summer, emission rates did not differ between previously damaged and undamaged trees at the site on the Western Slope of the Rocky Mountains, but rather tracked changes in the temperature and precipitation regime characteristic of the region. As the mid‐summer drought progressed at the Eastern Slope site, emission rates were low, but differences between previously damaged and undamaged trees were not statistically significant. Despite no difference in emissions, mid‐summer tissue monoterpene concentrations were significantly lower in previously damaged trees at both sites. With the onset of monsoon rains during late summer, emission rates from previously damaged trees increased to levels higher than those of undamaged trees despite the lack of herbivory. We conclude that (1) herbivory systemically increases the flux of terpenes to the atmosphere during the spring, (2) drought overrides the effect of past herbivory as the primary control over emissions during the mid‐summer, and (3) a release from drought and the onset of late‐summer rains is correlated with a secondary increase in emissions, particularly from herbivore‐damaged trees, possibly due to a drought‐delayed stimulation of induced monoterpene synthesis and/or increases in stomatal conductance. A greater understanding of the interactive effects of seasonality and herbivory on monoterpene emissions provides much needed information regarding the atmospheric and ecological consequences that these compounds will have for semiarid ecosystems.